Efficacy of novel water‐absorbing polymer amended soil for improving drought resilience of Solanum lycopersicum. Issue 1 (17th November 2022) - Rattan, Bharat; Saha, Abhisekh; Bordoloi, Sanandam; Garg, Ankit; Sahoo, Lingaraj; Sekharran, S.
Abstract: Climate change has exacerbated the frequency and duration of droughts. To sustain food production in such conditions, water storage and retention capacity of soil must be enhanced. Development of water‐absorbing polymer (WAP) from coal carbon residue (fly ash) can provide an economical and environmentally friendly alternative to commercial WAP for enhancing water retention and crop yield. The main objective of this study is to evaluate the growth performance of tomato species ( Solanum lycopersicum L.) under continued drought conditions in the presence of in‐house developed fly ash‐based WAP (FA‐WAP) against that of commercially available WAP (Com‐WAP). Quantification of the soil–water retention curve (SWRC) revealed an increase in plant wilting time and plant‐available water content (PAWC) in the order: control soil (no amendment) < Com‐WAP‐amended soil < FA‐WAP‐amended soil. Both the WAPs positively influenced the transpiration factors of crops in terms of stomatal conductance (SC) and photosynthetic yield under continued drought conditions. The yield parameters (i.e., the number of fruits, total weight, and shoot fresh biomass) increased by 82, 106, and 115%, respectively, in the case of FA‐WAP‐amended soil as compared with that of the control. Nevertheless, FA‐WAP provided 20% higher yield of tomato species during continued drought conditions than commercial WAP. The application of FA‐WAP can be an effective strategy to impart beneficial usage of FA waste by significantly reducing the irrigation frequency and irrigation water requirement without compromising the crop yield. It also ensures sustainable water stress management for a major food crop (tomato), thereby contributing towards United Nation's Sustainable Development Goals 2, 13, and 15. Core Ideas: Fly ash‐based water‐absorbing polymer (FA‐WAP) addition to soil increases water retention. FA‐WAP addition to soil increases plant wilting time and plant‐available water content. The number of fruits, total weight, and shoot biomass increased by 82, 106, and 115%, respectively, for FA‐WAP.